2010
DOI: 10.1002/agr.20256
|View full text |Cite
|
Sign up to set email alerts
|

Do consumers' attitudes and preferences determine their FAFH behavior? An application of the theory of planned behavior

Abstract: American consumers spend almost half of their food dollars on food away from home (FAFH) despite potential harmful effects of eating out more frequently. This study examines how consumers' attitudes toward FAFH and their personal preferences influence their behavior of eating food away from home. This study differs from previous work by using the Theory of Planned Behavior (TPB) to model consumers' FAFH behavior. Empirical testing of consumers' FAFH behavior reveals several interesting and important findings. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 25 publications
1
19
0
2
Order By: Relevance
“…Because of the behavioral basis of this study, the interview protocol included questions covering topics related to the constructs of health behavior theories. These theories included the socio-ecological model (Dresler-Hawke & Veer, 2006 ), social cognitive theory (Anderson, Winett, & Wojcik, 2007 ), the theory of planned behavior (Bhuyan, 2011 ), and the health belief model (Orji & Mandryk, 2014 ). These theories were included as several studies had used them in relation to understanding eating behaviors (Anderson et al, 2007 ; Kothe, Mullan, & Butow, 2012 ; Lindsay, Sussner, Greaney, & Peterson, 2009 ).…”
Section: Methodsmentioning
confidence: 99%
“…Because of the behavioral basis of this study, the interview protocol included questions covering topics related to the constructs of health behavior theories. These theories included the socio-ecological model (Dresler-Hawke & Veer, 2006 ), social cognitive theory (Anderson, Winett, & Wojcik, 2007 ), the theory of planned behavior (Bhuyan, 2011 ), and the health belief model (Orji & Mandryk, 2014 ). These theories were included as several studies had used them in relation to understanding eating behaviors (Anderson et al, 2007 ; Kothe, Mullan, & Butow, 2012 ; Lindsay, Sussner, Greaney, & Peterson, 2009 ).…”
Section: Methodsmentioning
confidence: 99%
“…Previous research articulated TPB as one of the key expectative-value models to analyze food-related behavioral intention. For example, several studies concentrated on the TPB model investigating healthy eating (Payne et al, 2005), green food purchasing (Ham et al, 2015), halal food purchasing (Soon & Wallace, 2017), and choices for food-away-from home (Bhuyan, 2010). In this study, food safety and delivery hygiene are essential determinants for explaining behavioral intention and continuance behavior.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…Healthy food availability and access is a means of living for everyone. However, due to swiftly skyrocketed FF restaurants in USA, health and eating out have largely shown that eating food away from home adversely impacts an individual's health, including contributing to obesity (Bellemare et al, 2017;Bhuyan, 2011). In other words, consumers understand that meals and snacks consumed away from home are typically less healthful than foods prepared at home (Anderson et al, 2011;Brown et al, 2000;Lin et al, 1999).…”
Section: Health Risks In Consumption Of Fast-foods and Street Foodsmentioning
confidence: 99%